Strain improvement of penicillium janthinellum ncim 1171 for increased cellulase production - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Varma, Anjanikumar; Gokhale, D. V. (Bioresource Technology, 2007)
The strain of Penicilhuinjanthinellunt NOM 1171 was subjected to mutation involving treatment of Ethyl Methyl Sulfonate (EMS) for 24 h followed by UV-irradiation for 3 min. Successive mutants showed enhanced cellulase production (EMS-UV-8), clearance zone on Avicel containing plate (SM2) and rapid growth on Walseth cellulose agar plates containing 0.2% 2-deoxy-D-glucose (SM3). These mutants were transferred to Walseth cellulose plates containing higher concentration (1.5%) of 2-deoxy-D-glucose (SM4) in which only five mutants showed clearance zone on SM4. All these mutants showed approximately two-fold increase in activity of both FPase and CMCase in shake flask culture when grown on basal medium containing CP-123 (1%) and wheat bran (2.5%). The enzyme preparations from these mutants were used to hydrolyze Avicel. Higher hydrolysis yields of Avicel were obtained with enzyme preparations of EU1. This is the first report on the isolation and selection of mutants based on hydrolysis of Avicel, which is the most crystalline substrate. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 2-deoxy-D-glucose resistant mutants; cellulase activity; EMS and ultraviolet mutation; Penicillium janthinellum